Augmented Reality on Museums: the Ecomuseu Virtual Guide - Teixeira, Natalia; Lahm, Bianca; Peres, Fabiana Frata Furlan; Mauricio, Claudio Roberto Marquetto; Xavier Natario Teixeira, Joao Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
Studies point that smartphones show an important role in the improvement of museum visitors experience. Based on that, a virtual guide prototype was developed to enhance the museum visitors experience inside a famous attraction from Foz do Iguaçu, the Ecomuseu. The developed application inserts virtual elements in different locations of the museum. To validate the proposed solution, we tested the app with 15 different users. Due to the COVID-19 pandemic, we adapted the app and performed the evaluation over the virtual tour of the same museum, which is available online. Despite the difficulties imposed by the current context, the feedback from the tested users was very positive.